Estudo da memória de trabalho em adultos e idosos normais - Siqueira, Larissa de Souza (2006)
This study has the objective of investigating the performance of adults and seniors in terms of working memory skills and at the Mini-Exam of Mental State, verifying how these skills relate to each other, to the age and to the scholarship level. The sample was composed by 34 people, with ages among 37 and 83 years-old, Brazilians, Portuguese speakers, literate and without any evident and referred neurological and/or cognitive alterations and it was shared into four groups according to the age group. The adults and seniors performance at the working memory assessments was checked through the repetition of non-words task to assess specifically the phonological memory and the repetition of a sequence of digits to assess the central executive and the phonological memory, according to Baddeley and Hitch s proposal (1974 apud GATHERCOLE & BADDELEY, 1993). The Mini-Mental State Examination, Folstein and McHugh s proposal (1975), was used to assess the orientation, immediate memory, attention, calculation, mandate, language, reading and constructive praxis. In order to analyze the co-relation among the evaluations it was used the non parametric test, the Sperarman s Correlation Coefficient, from which it was identified: 1) the younger people had a better performance at the three tasks applied when compared with the older ones; 2) there was a significant correlation between the repetition of non-words and repetition of a sequence of digits tasks; 3) the Mini-Mental State Examination has a small correlation with the memory working tasks; 4) it was observed significant correlation of age and scholarship with the tasks of repetition of non-word, repetition of a sequence of digit and Mini-Mental State Examination. Comparing the four groups, it was verified that the rightness average at the three assessmests diminished as much as the age group increased. It was observed that the rightness averages at the working memory and Mini- Mental State Examination tasks increased according to the scholarship level. It concluded that older people with low scholarship level, considered as a group not individually, present smaller performance at the working memory and Mini-Mental State Examination tasks than younger people and with higher scholarship level